ИНГЛИЗ ТИЛИНИ ЎРГАНИШДА ТАЛАБАЛАРНИНГ ИЖТИМОИЙ-КОММУНИКАТИВ ФАОЛЛИГИНИ ОШИРИШДА БАДИИЙ АДАБИЁТЛАРНИНГ ЎРНИ - Кунназарова, Г. (SCIENCE and SOCIETY, 2022)
Students' social-communicative activity is important for their successful learning of English. After all, English, like all foreign languages, is effectively mastered in the process of active social-communicative relations. The article describes the issue of increasing social and communicative activity of students in learning English by means of fiction.
Keywords: English language; student; activity; social-communicative activity; increase of social-communicative activity; fiction